C14orf132 gene is possibly related to extremely low birth weight. Issue 1 (December 2016) - Tiirats, Airi; Viltrop, Triin; Nõukas, Margit; Reimann, Ene; Salumets, Andres; Kõks, Sulev
Abstract Background Despite extensive research the genetic component of extremely low birth weight (ELBW) in newborns has remained obscure. Results The aim of the case study was to identify candidate gene(s) causing ELBW in newborns and hypotrophy in infants. A family of four was studied: mother, father and two ELBW-phenotype children. Studies were made of the medical conditions of the second child at birth and post-partum - peculiar phenotype, micro-anomalies, recurrent infections, suspicion of autoimmune hepatitis, multifactorial encephalopathy and suspected metabolic and chromosomal abnormalities. Whole genome single nucleotide polymorphism (SNP) genotyping array was used to investigate the genomic rearrangements in both affected children using peripheral blood DNA samples. Whole blood transcriptome was assessed by using RNA sequencing (RNA-seq) in all four family members. RNA-seq identified a single gene –C14orf132 (chromosome 14 open reading frame 132) differentially expressed, with the level of the transcript significantly lower in the blood samples of the children. Copy number variant (CNV) analysis did not reveal any pathogenic CNVs in the region ofC14orf132 gene of both affected children. Conclusion We demonstrated the importance of combining whole genome CNV and transcriptome analysis in identification of the candidate gene(s) in case studies. We propose theC14orf132 gene expression to be associated with the ELBW-phenotype.C14orf132 gene is a novel long non-coding RNA (lincRNA) with unknown function, which might be associated with the pre- and early postnatal developmental delay through the altered gene expression.